Ankle-Brachial Index as a Predictor of Mortality in Hemodialysis: A 5-Year Cohort Study - Miguel,Jair Baptista (2017)
Abstract Background: Abnormal ankle-brachial index (ABI) has been found to be a strong predictor of mortality in some hemodialysis populations in studies with relatively short periods of follow-up, lower than 2 years. Objective: This study aimed to assess the predictive value of abnormal ABI as a risk factor for death among patients on maintenance hemodialysis after a 5-year follow-up. Methods: A total of 478 patients on hemodialysis for at least 12 months were included in the study. ABI measurement was performed using a mercury column sphygmomanometer and portable Doppler. Patients were divided into 3 groups according to ABI (low: <0.9; normal: 0.9 to 1.3; and high: >1.3) and followed for a 60-month period. Results: The prevalence rates of low, normal and high ABI were 26.8%, 64.6% and 8.6%, respectively. The 5-year survival rate was lower in the groups with low ABI (44.1%, P<0.0001) and high ABI (60.8%, P= 0.025) than in the group with normal ABI (71.7%). Cox regression was used to evaluate the association between ABI and mortality, adjusting for potential confounders. Using normal ABI as reference, a low, but not a high ABI was found to be an independent risk factor for all-cause mortality (HR2.57; 95% CI, 1.84-3.57 and HR 1.62; 95% CI, 0.93-2.83, respectively). Conclusions: long-term survival rates of patients with either low or high ABI were lower than the one from those with normal ABI. However, after adjustment for potential confounders, only low ABI persisted as an independent risk factor for all-cause mortality among hemodialysis patients.